Nutrition security in Zambia through policies adaptive to climate extremes - Jennings, Steward; Challinor, Andrew J.; Sarku, Rebecca; Macdiarmid, Jennie; King, Richard; Pope, Edward; Chomba, Christian; Nawiko, Masiye; Nkanyani, Shiluva Chauke; Horgan, Graham; Hellin, Jon; Ng'endo, Mary; et al. (University of Leeds, 2024)
Adaptive options for nutrition security in Africa are constrained by limited knowledge of climate extremes, and a focus on calorific, rather than nutritional, outcomes. Accordingly, we assess the impacts of extreme future years on national-level calorie and nutrient supply in Zambia for both business-as-usual and nutrition focus policy scenarios. We conclude with specific policy options for Zambia, drawing out relevance to the wider region and key barriers and enablers.